Investigation of polymer electrolyte based on agar and ionic liquids - M. M. Silva; R. Leones; F. Sentanin; L. C. Rodrigues; I. M. Marrucho; J. M. S. S. Esperanca; A. Pawlicka (eXPRESS Polymer Letters, 2012)
The possibility to use natural polymer as ionic conducting matrix was investigated in this study. Samples of agarbased electrolytes with different ionic liquids were prepared and characterized by physical and chemical analyses. The ionic liquids used in this work were 1-ethyl-3-methylimidazolium ethylsulfate, [C2mim][C2SO4], 1-ethyl-3-methylimidazolium acetate, [C2mim][OAc] and trimethyl-ethanolammonium acetate, [Ch][OAc]. Samples of solvent-free electrolytes were prepared and characterized by ionic conductivity measurements, thermal analysis, electrochemical stability, X-ray diffraction, scanning electron microscopy and Fourier Transform infrared spectroscopy. Electrolyte samples are thermally stable up to approximately 190°C. All the materials synthesized are semicrystalline. The electrochemical stability domain of all samples is about 2.0 V versus Li/Li+. The preliminary studies carried out with electrochromic devices (ECDs) incorporating optimized compositions have confirmed that these materials may perform as satisfactory multifunctional component layers in the field of ‘smart windows’, as well as ECD-based devices.